Psicoterapia di gruppo: la prassi, la formazione, la ricercai gruppo: la prassi, la formazione, la ricerca - Mocci, Antonia; Anzilotti, Carlo; Bensi, mARCO; Barra, simone; Fiori Nastro, Paolo (Il sogno della farfalla, 2009)
The aim of this study is to conduct research into the activity carried out by 118 psychotherapists whose work is based on the theory and practice of Massimo Fagioli and constitute the editorial committee of this journal. In order to make this survey possible a questionnaire containing 28 questions was prepared and sent to them. 82 answers were obtained, constituting 69,5% of the group interviewed. We started off considering general characteristics, such as the number of therapists carrying out this profession and the number of patients in treatment. Then followed more specific information, such as the characteristics of the therapists, of the groups, patients and the factors implied in the process of curing mental illness. We tried to understand the working method adopted and how psychotherapy sessions are conducted from the answers. We tried to outline this practice in its more peculiar aspects, trying to identify the different methods compared to other theories and techniques. The results revealed that we are dealing with a group practice carried out by a consistent number of therapists with a fair amount of professional experience. The therapist have a considerable number of patients, estimated at 1568. Many differences emerge with what is reported in the literature starting from the criteria adopted for the admission and dismissal of patients. The data which emerge on the therapeutic factors are completely different from those recognized by other forms of group psychotherapy. The therapists interviewed believe that the principle therapeutic factors are the personal identity of the therapists, the interpretation of dreams and the interpretation of the therapeutic relation. These results imply that the human formation and professional training of the therapist is very important.